POSTMODERNISM AND POSITIVISM - Evaldas Nekrašas (Problemos)
Positivism is a favorite object of postmodernist attacks. With an interesting exception, namely Hume, it is regarded by postmodernists as an embodiment of everything what is the worst in the Spirit of Enlightenment: its emphasis on wholeness, unity, and unequivocalness of knowledge. There is no doubt that in many of its orientations postmodernism differs from positivism. However, it shares with positivism and, especially, logical positivism many important epistemological features including those it pretends to be anti-positivist: first of all, relativism and fallibilism. Social orientation of postmodernism shows a remarkable similarity to that of positivism also. There is no reason to regard postmodernism as a revolution in philosophy which overcame all modernist philosophies, positivism including.